Model Construction and Performance Degradation Characteristics of a Deflector Jet Pressure Servo Valve under the Condition of Oil Contamination - Yuanbo Chu; Zhaohui Yuan; Xuegong He; Zhichao Dong (International Journal of Aerospace Engineering)
The deflector jet pressure servo valve is a kind of high-precision hydraulic component that can be widely used in the antiskid braking system of an aircraft. In actual service, it will be faced with extreme working conditions of gradual oil contamination, which will cause performance degradation and function maladjustment of the whole valve. To this end, the paper proposes a performance degradation characteristic analysis method. In which, firstly, the structural characteristics and working principle of the deflector jet pressure valve are analyzed; then, the entire dynamics model of the pressure valve is built using the braking cavity as the load blind cavity. Secondly, the two main failure modes induced by oil contamination such as erosion wear of pilot stage and stuck of slide valve stage’s valve core are determined based on the engineering experience, aimed at which the failure mechanism is analyzed; then, the sensitivity simulation model of the servo valve’s output pressure with respect to key degradation parameters is established and the sensitivity analysis is performed. Finally, combining the theoretical analysis with multiphysics simulation correction methods, the performance degradation model of the typical failure modes are established, and then, the performance degradation characteristics under dynamic contamination conditions are analyzed, which is combined with the failure threshold determined by the dynamics simulation to finish the service life prediction of the deflector jet servo valve.